The Effect of Education and Training Program, Facilities and Infrastructure Completeness, Organizational Support on Employee Performance Through Satisfaction as Variable Mediation - Yuniarti Yuniarti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the effect of education and training programs, infrastructure completeness, organizational support on employee performance through satisfaction as a mediating variable. The research method used in this study is a quantitative method. Quantitative research methods are designed to test existing hypotheses. Respondents in this study were 100 training participants. The data analysis used a structural approach to the Equation Model (SEM) assisted by the smart PLS application. There is a significant positive effect between the Education and Training Program variables on employee performance. There is a significant positive effect between the infrastructure completeness variable on employee performance. There is a significant positive effect between organizational support on employee performance. There is a significant positive effect between satisfaction on employee performance. There is a significant positive effect between education and training on satisfaction. There is a significant positive effect between infrastructure completeness on satisfaction. There is significant negative effect between Organizational Support on Satisfaction. There is a significant positive effect between Education and Training Programs on employee performance mediated by satisfaction. there is a significant positive effect between Infrastructure completeness on employee performance mediated by satisfaction. There is a significant negative effect between Organizational Support on employee performance mediated by satisfaction